Genotypic variation and stability for nitrogen use efficiency in winter wheat. Issue 1 (27th January 2020) - Brasier, Kyle; Oakes, Joseph; Balota, Maria; Reiter, Mark; Jones, Ned; Pitman, Robert; Sneller, Clay; Thomason, Wade; Griffey, Carl
Abstract: Wheat ( Triticum aestivum L.) products account for a large portion of the total dietary calories and protein consumed globally, thus requiring efficient N management systems for optimal grower profitability and to reduce negative environmental impacts of nontarget fertilization. This investigation sought to evaluate genotypic variation for N use efficiency (NUE), assess yield stability, and validate traits for improvement of crop performance across N rates. Three separate studies were conducted over four growing seasons in the eastern United States that varied in the number of N rates and site‐seasons. Study I was conducted using five N rates over three site‐seasons, Study II was conducted using three N rates over six site‐seasons, and Study III was conducted using two N rates over nine site‐seasons. Genotype × N rate interactions were more frequently observed for grain yield when three or more N rates were used in the experimental design. The three studies identified significant genotypic variation for NUE and identified wheat lines that consistently expressed high grain yields over N‐site‐seasons. Aboveground biomass at physiological maturity was strongly associated with grain yield in Study II when 67 kg N ha −1 ( r = .66, P ≤ .05) was applied and in Study III when 67 kg N ha −1 ( r = .71, P ≤ .05), and 134 kg N ha −1 ( r = .89, P < .001) was applied. Findings from this investigation inform soft red winter wheat breeders on diverse sources of breeding materials and target traits to improve NUE.